Factors regulating hippocampal neuronal proliferation, differentiation and survival - Jie, Lu (2004)
Neural development is controlled by the temporal and spatial coordination of intrinsic and extrinsic factors that may be brain region-specific. In this work, the regulation of postnatal hippocampal neuronal proliferation, differentiation and apoptosis by extrinsic factors including glucocorticoids, neurotransmitters and cytokines was investigated. Hippocampal and cerebellar granule neuronal cultures were used to identify factors which may be responsible for the differential developmental patterns displayed by granule neurons in cells from these morphologically similar brain areas, and the signaling pathways employed were also studied. Other in vitro studies were done to examine the mechanisms underlying glucocorticoid-induced apoptosis in the hippocampus, in particular with regard to the role of glutamatergic transmission. Results show that transforming growth factor β2 (TGF-β2), supported by the Smad signaling machinery, plays a key role in determining hippocampal cell fate by inhibiting proliferation and, in parallel, inducing neuronal maturation. Brain-derived neurotrophic factor (BDNF), better known for Trk receptor-mediated promotion of neurogenesis and differentiation, was found to exert anti-proliferative and pro-neuronal effects on developing hippocampal neurons by activating a MAP kinase cascade which interacted with the TGF-β signaling pathway. The glucocorticoid dexamethasone (DEX) was found to directly induce apoptosis in hippocampal cell cultures through the mediation of glucocorticoid receptors (GR); this effect could only be demonstrated if neuroprotective mineralcorticoid receptors (MR) were antagonized. Further, it was shown that mature, rather than immature, granule neurons are targeted by glucocorticoids for apoptosis. Additional experiments showed that glucocorticoid actions at least partially depend on the prevailing glutamatergic status. The apoptotic actions of DEX are, at least partly, mediated by NMDA andmetabotropic glutamate receptors. Low doses of NMDA, acting via the synaptic NMDA receptor (NMDAR) were shown to efficiently block DEX-induced hippocampal cell death. Evidence was obtained to show that glucocorticoid-induced apoptosis in hippocampal cells is mediated by NMDAR as well as metabotropic receptors. Thus, the final outcome of glucocorticoid treatment on hippocampal cell survival depends on the convergence and integration of transcriptional signals and signals originating at the cell membrane. In conclusion, these studies have identified some of the factors and signaling pathways contributing to the orchestrated neurodevelopment of hippocampal, as well as cerebellar, neurons.